Dynamics of the agricultural frontier in the Amazon and savannas of Brazil: analyzing the impact of policy and technology - Smith, J.; Winograd, Manuel; Gallopin, G.; Pachico, Douglas H. (1998)
While many goverment policies stimulating deforestation have been reserved, private sector lobbies for uncontrolled logging and soybean export corridors threaten the Amazon. Under a favorable scenario (macroeconomic stabilization, controlled logging and road building, sustainable technologies, global environmental markets) reconversion of natural habitat could be 30% lower than under unfavorable policies and technologies, without sacrificing production